1960
DOI: 10.1177/00220345600390030401
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Periodontal Disease in a Hospitalized Population

Abstract: This study was designed to measure the prevalence of periodontal disease in a hospitalized population and to determine whether persons with confirmed diagnoses of specific diseases demonstrate a greater prevalence of periodontal disease than those who are in relatively good health. EXPERIMENTAL METHODSDescription of sample.-The sample studied was drawn from patients who were hospitalized at the Veterans Administration Hospital, Brooklyn, New York. Veterans comprised a large proportion of the total male populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1962
1962
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 13 publications
0
20
1
Order By: Relevance
“…The numbers of cases among those reporting recent alcohol intake of 0.1-4.9 g/day were 550; 5.0-14.9 g/day, 562; 15-29.9 g/day, 276; for > 30 g/day, 288; and for non-drinkers, 449. intake and periodontitis. Early studies observed increased prevalence and severity of periodontal disease among patients with cirrhosis (Sandler and Stahl, 1960;Movin, 1981), and attributed this to poor oral hygiene (Movin, 1981). Other studies reported worse periodontal conditions in alcoholic patients with and without cirrhosis than in healthy subjects (Dunkley and Carson, 1968;Novacek et al, 1995) and in nonalcoholic patients with cirrhosis (Novacek et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of cases among those reporting recent alcohol intake of 0.1-4.9 g/day were 550; 5.0-14.9 g/day, 562; 15-29.9 g/day, 276; for > 30 g/day, 288; and for non-drinkers, 449. intake and periodontitis. Early studies observed increased prevalence and severity of periodontal disease among patients with cirrhosis (Sandler and Stahl, 1960;Movin, 1981), and attributed this to poor oral hygiene (Movin, 1981). Other studies reported worse periodontal conditions in alcoholic patients with and without cirrhosis than in healthy subjects (Dunkley and Carson, 1968;Novacek et al, 1995) and in nonalcoholic patients with cirrhosis (Novacek et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…One well‐known effect associated with diabetes is gingival inflammation (38,39). Neither gingival inflammation, nor macroscopic alterations of oral mucosa were observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The American Society of Diabetes defined periodontal disease as the sixth complication of diabetes in 1997;1,2 Diabetes raises the risks of developing periodontal disease and affects its severity 3,4. Individuals with diabetes tend to have higher values for indices of plaque, dental calculus, and gingival inflammation, and deeper periodontal pockets 5.…”
Section: Introductionmentioning
confidence: 99%